2022
DOI: 10.1302/0301-620x.104b6.bjj-2022-0127
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of metalwork failure and nonunion after hindfoot Charcot reconstruction

Abstract: Aims Surgical reconstruction of deformed Charcot feet carries a high risk of nonunion, metalwork failure, and deformity recurrence. The primary aim of this study was to identify the factors contributing to these complications following hindfoot Charcot reconstructions. Methods We retrospectively analyzed patients who underwent hindfoot Charcot reconstruction with an intramedullary nail between January 2007 and December 2019 in our unit. Patient demographic details, comorbidities, weightbearing status, and post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Najefi et al identified a 19% metal work failure rate following Charcot hindfoot reconstruction performed using a hindfoot nail ( 11 ). Kummen et al reported a higher major hardware failure of 24% among all Charcot foot reconstructions performed using internal fixation technique that included combined hindfoot and midfoot procedures ( 1 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Najefi et al identified a 19% metal work failure rate following Charcot hindfoot reconstruction performed using a hindfoot nail ( 11 ). Kummen et al reported a higher major hardware failure of 24% among all Charcot foot reconstructions performed using internal fixation technique that included combined hindfoot and midfoot procedures ( 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…This is combined with preparation of the medial gutter of the ankle joint ( Figure 3B ). Preservation of the medial malleolus during the preparation of the medial gutter is beneficial in improving the fixation construct and the outcomes ( 11 ). Subtalar joint is accessed and released.…”
Section: Surgical Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…The results of Charcot reconstruction may be slowly improving. In a retrospective review of 70 patients who underwent hindfoot Charcot reconstruction with an intramedullary nail, Najefi et al 46 reported an 83% overall hindfoot union rate at a mean follow-up of 54 months. A greater nail diameter-to-isthmus ratio (p = 0.034) and supplemental hindfoot compression screws (p = 0.038) were associated with a higher union rate.…”
Section: Charcot Arthropathymentioning
confidence: 99%
“…The aim of this study from London (UK) was to identify the factors related to the suboptimal hindfoot-specific outcomes, including recurrent deformity and nonunion, in patients undergoing hindfoot Charcot reconstruction with a standard hindfoot IMN. 4 A database of patients who underwent hindfoot Charcot reconstruction using an IMN between January 2007 and December 2019 was used to identify the study cohort. Patients who had a hindfoot reconstruction with plates or screws or a circular fixator, and those with less than one year of follow-up, were excluded.…”
Section: Predictors Of Failure In Hindfoot Charcot Reconstructionmentioning
confidence: 99%